Duplex PCR-based assay for simultaneous detection of tristeza and greening diseases in citrus - A.K. DAS, DILIP GHOSH* and (Indian Phytopathology, 2012)
Citrus tristeza virus (CTV), an aphid transmitted RNA virus having a genome size of about 19.3 kb singly or as a mixed infection with Candidatus liberibacter asiaticus (CLa), a phloem-limited, uncultured bacterium causing citrus greening disease (Huanglongbing/HLB) play a significant role to cause citrus decline in India. Since citrus is predominantly a vegetatively propagated crop, rapid detection techniques are essential in preventing spread of these two graft transmissible diseases through infected planting material. A rapid and reliable duplex PCR based detection protocol has been standardized. Sets of primers designed on the basis of respective pathogen isolate sequence data available in GenBank were synthesized and used in the present experiment to obtain anticipated products of calculated size. Using duplex PCR two different fragments of ~ 700 bp and ~ 1160 bp specific to CTV and CLa respectively were simultaneously amplified. The consistent result of duplex PCR was compared with simplex PCR for detection of each pathogen. The duplex PCR method developed in the present investigation proved to be highly sensitive, economic and reliable method for detection of both CTV and CLa in citrus plants not only for eradication of pathogen infection from the existing citrus orchard or for plant varietal improvement programme but more importantly in implementing citrus budwood certification programme to obtain disease-free planting material.